Strategy to Increasing Country's Economic Growth With a Bonded Zone Logistic Center and Free Trade - Sri Yanthy Yosepha; Agus Suhendra; Christophorus Indra Wahyu Putra; Kamsariaty Kamsariaty; Denny Mahendra (Greenation International Journal of Economics and Accounting, 2024)
Articles can make a significant contribution to the economic literature and public policy, as well as provide practical guidance for policymakers and stakeholders in their efforts to improve economic growth through logistics and free trade strategies. The research method applied in this scientific article is a structured literature review. Relevant scientific articles are selected, identified, and evaluated during the literature review process. The determination of the scope of the study was carried out using the PICO (population/problem, intervention, comparison) framework, which provides a score to set the study limits. A collection of relevant scientific articles is selected, identified, and reviewed during a literature review. The results of this article state that existing logistics infrastructure plays an important role in improving logistics performance, which ultimately has an impact on increasing sea trade and higher economic growth. Cooperation with customs and excise authorities in the supply chain also increases trade opportunities and supports environmental sustainability by reducing carbon emissions through reduced waiting times and queues. The use of green energy sources and green practices in logistics operations not only reduces negative environmental and social impacts, but also improves financial performance through increased GDP per capita, trade openness, and greater global export opportunities.